We need to talk: Or do we? Geographic distance and the commercialization of technologies from public research - Guido Bünstorf; Alexander Schacht (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Using a new dataset with detailed geographic information about licensing activities of the Max Planck Society, Germany's largest non-university public research organization, we analyze how the probability and magnitude of commercial success are affected by geographic distance between licensors and licensees. Our evidence suggests that proximity is not generally associated with superior commercialization outcomes. A negative association between distance and commercialization success is identified only for the specific cases of, first, spin-off licensees located outside Germany and, second, foreign licensees within the subsample of inventions with multiple licensees.
Keywords: L24; L26; O34; R30; 330; academic inventions; licensing; spin-off entrepreneurship; geographic distance; Öffentliche Forschung; Lizenzvergabe; Forschungskooperation; Betriebsaufspaltung; Entfernung; Deutschland